2006
DOI: 10.1097/01.mpg.0000221888.36501.f2
|View full text |Cite
|
Sign up to set email alerts
|

Superior Mesenteric Artery Syndrome in Children

Abstract: SMAS usually presents more acutely than chronically with symptoms of small bowel obstruction. Weight loss is not necessary for SMAS development. Prior neurological injury may be a risk factor for development of SMAS. Upper gastrointestinal radiography remains the primary means of diagnosis. SMAS is typically successfully managed medically. Surgical intervention should be reserved for patients' refractory to medical therapy. The expected outcome of SMAS is excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
203
3
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(221 citation statements)
references
References 19 publications
12
203
3
3
Order By: Relevance
“…The largest series in pediatric age group is 22 children diagnosed and followed up as SMAS reported by Biank et al (4).The vast majority of patients admitted had more than one symptom (64%). In this study, patients were diagnosed by gastrointestinal series 18 patients (82%), abdominal computed tomography 2 patients (9%) and laparotomy 2 patients (9%).…”
Section: Discussionmentioning
confidence: 99%
“…The largest series in pediatric age group is 22 children diagnosed and followed up as SMAS reported by Biank et al (4).The vast majority of patients admitted had more than one symptom (64%). In this study, patients were diagnosed by gastrointestinal series 18 patients (82%), abdominal computed tomography 2 patients (9%) and laparotomy 2 patients (9%).…”
Section: Discussionmentioning
confidence: 99%
“…Our patient developed acute-onset SMAS. Although SMAS has commonly been reported to present as a chronic condition in adulthood, one pediatric study reported that SMAS was more likely to present acutely, with sudden onset of symptoms related to bowel obstruction [7]. It may be difficult to distinguish whether gastrointestinal symptoms of patients with eating disorders result from the eating disorders themselves or from chronic SMAS associated with the eating disorders [3].…”
Section: Discussionmentioning
confidence: 99%
“…Bu klinik durum erişkinlerde yapılan çalışmalara göre kadınlarda ve genç erişkinlerde (10-39 yaşları arasında) daha sık görülmektedir (6,34,36). Bizim olgularımız da adölesan çağındaki hastalardı.…”
Section: Tedaviunclassified